IGC: A Play-based Approach to Improve Concept and Operations on Integers - Analiza B Tanghal (ASEAN Multidisciplinary Research Journal, 2020)
This study aimed to determine the impact of Integer Game Card in increasing the performance of Grade 7 students in operations of integers. The research used the One Group Pretest-Posttest design. There were five Grade 7 sections with a total of 196 respondents (89 male and 107 female) who participated in the study. The data obtained were processed through Strata using the following statistical techniques: mean, weighted mean and dependent t-test. Results revealed that the students increased their performance in operations on integers through the use of game card called Integer Game Card Battle. It also implies that the game card has a significant impact in the performance of students in operations on integers. The study recommends that the Integer Game Card Battle should be implemented in Grade 7 students regularly until they master operations on integers especially how to determine the appropriate sign of the integers. Encourage Elementary Grade 6 Math Teacher to use Integer Game Card Battle in developing the skills of their pupils in the four fundamental operations on integers.